Reduced-order modelling using nonlinear modes and triple nonlinear modal synthesis. (1st July 2018) - Joannin, Colas; Thouverez, Fabrice; Chouvion, Benjamin
Highlights: A new reduced-order modelling method to study vibrations in nonlinear systems is proposed. The approach makes use of nonlinear modes and characteristic constraint modes. The method is tested on a finite element model of mistuned bladed-disk subjected to dry friction. Excellent computational performance is achieved. Abstract: This paper introduces a novel reduced-order modelling technique well-suited to the study of nonlinear vibrations in large finite element models. The method combines the concepts of nonlinear complex modes and characteristic constraint modes – or interface modes – to build a fully algebraic reduced-order model easily solved by standard iterative solvers. The performance of the method is appraised on a nonlinear finite element model of bladed disk in the presence of structural mistuning, highlighting the potential of this new technique to deal with current industrial problematics.